PROBLEMS AND SIMULATION METHODS OF DISTRIBUTED OBJECTS - Nikita V. Kudinov (Advanced Engineering Research)
Problems, methods and results of the simulation programs development as well as their algorithmic support and software are considered. The problems are discussed in terms of the technologic distributed objects, such as the main gas pipeline division and the material multilayered structure where thermal processes take place.